HASIL BELAJAR IPAS MENGGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN PERMAINAN ENGKLEK PADA KELAS V SDN UNDAAN LOR 2 - Fitriya, Aryanti Nurul; Su’ad, Su’ad; Kuryanto , Moh Syafruddin (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
The aim of this research to improve IPAS learning outcomes using the Teams Games Tournament learning model assisted by the Engklek game. Teams Games Tournament is a learning model where students are able to learn actively, practicing responsibility for the tasks given by their teacher with their group members. This research uses a classroom action research method which consists of 2 cycles, each cycle consisting of two meetings. Data collection techniques in this research are interviews and tests. The research instruments used were interview sheets and test questions. The data analysis techniques in this research are qualitative and quantitative analysis. The research results show an increase in IPAS learning outcomes. In the first cycle of classical completion, student learning outcomes were 55.55% with the